MODEL ADOPTION OF GENERAL PLAN INFORMATION SYSTEM PROCUREMENT OF KPA UDAYANA UNIVERSITY (SIRUPKU) - Agung Suaryana, I Gusti Ngurah; Noviari, Naniek; Eka Damayanthi, I Gst Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023, 2023)
The information system is an important resource in the organization in the context of efficient and transparent implementation of activities. One of the information systems implemented at Udayana University is the Information System for the General Plan of Procurement of KPA Udayana University (SiRUPKU). This study identifies the factors that explain the successful implementation of SiRUPKU at Udayana University. This study uses the UTAUT model to explain the user's interest and behavior in using the SiRUPKU application in the packaging process for the procurement of goods and services at Udayana University. There are four main factors that explain interest and behavior in using SiRUPKU, namely performance expectations, business expectations, social influences, and facilitating conditions. The research population is all using the SiRUPKU application, namely PPK and KDP supporters at Udayana University. The entire population became the research sample. Data were collected using a questionnaire. This study succeeded in collecting 83 questionnaires from 86 questionnaires distributed. The data were analyzed by partial least squares (PLS). The results of the study prove that performance expectations, business expectations, social influences, and facilitating conditions have a positive effect on interest in using SiRUPKU. Interest in using SiRUPKU has a positive effect on behavior in using SiRUPKU.